Fresh‐frozen plasma transfusion did not reduce 30‐day mortality in patients undergoing cardiopulmonary bypass cardiac surgery with excessive bleeding: the PLASMACARD multicenter cohort study. Issue 4 (30th September 2013) - Doussau, Adélaïde; Perez, Paul; Puntous, Maryse; Calderon, Joachim; Jeanne, Michel; Germain, Christine; Rozec, Bertrand; Rondeau, Virginie; Chêne, Geneviève; Ouattara, Alexandre; Janvier, Gérard; PLASMACARD Study Group
<x xml:space="preserve">Abstract</x> Background During on‐pump cardiac surgery, hemorrhagic complications occur frequently. Fresh‐frozen plasma (FFP) is widely transfused to provide coagulation factors. Yet, no randomized clinical trial has demonstrated its benefits on mortality. We assessed the relationship between therapeutic transfusion of FFP and 30‐day mortality in cardiac surgery patients suffering from excessive bleeding in a prospective cohort study. Study Design and Methods Adult patients who underwent on‐pump cardiac surgery and experienced excessive bleeding during the 48‐hour perioperative period were recruited from 15 French centers between February 2004 and January 2006. Patients who received a preventive FFP transfusion were excluded. The association between FFP transfusion and all cause 30‐day mortality was estimated using a Cox proportional hazards model, adjusted for confounding. A propensity score (PS) sensitivity analysis was also performed. Results Among 967 patients included in this study, 58.1% received FFP. The median dose was 11.3 mL/kg (interquartile range, 7.6‐19.5). The cumulative 30‐day mortality rate was 11.3% (95% confidence interval [CI], 9.5‐13.5). FFP transfusion was associated with a higher 30‐day mortality (hazard ratio [HR], 3.2; 95% CI, 1.7‐6.1) in univariate analysis; however, after adjusting for prognostic factors, there was no longer any association (HR, 1.5; 95% CI, 0.8‐3.0, p = 0.20). The results of the PS analysis were consistent with the adjusted analysis. Conclusion Among on‐pump cardiac surgery patients experiencing excessive perioperative bleeding, there is no evidence of a beneficial impact of FFP transfusion on mortality.